Ward level analysis of standardized nursing data – example of the FinCC use - Mykkänen, Minna; Ahonen, Outi; Kinnunen, Ulla-Mari; Saranto, Kaija (Finnish Journal of eHealth and eWelfare, 2023)
The use of the standardized nursing terminology makes patient care transparent. It enables the description nursing care processes and generating knowledge for decision-making and management. The structure of the Finnish Care Classification (FinCC) structures the documentation of nationally agreed core nursing data: nursing diagnoses, interventions, and outcomes. The purpose is to analyze the use of FinCC to record nursing diagnoses, interventions and outcomes in electronic health records in three hospitals. In this descriptive study, appropriate sampling from data repositories in the Internal Medicine wards of three hospitals was applied. The research data consisted of anonymous ward-level data collected over a six-month period. The data was analyzed according to the distributions of the use of FinCC's component, main and subcategory levels. According to the results, the process phases of nursing diagnoses, interventions and outcomes are used in all hospitals. All three levels of FinCC (component, main and subcategories) were used to document nursing care. Mainly, the documentation of diagnoses and interventions were carried out at the main and subcategories levels, with the exception of one hospital, where part of the diagnoses were documented using the component level. In addition, in two hospitals, the diagnoses were documented directly at the diagnoses phase of the process, without using the component, main or subcategory level. All hospitals used all components of FinCC to describe diagnoses and interventions, with the exception of one hospital where the component Life Cycle was not used to document interventions. Standardized nursing data from data repositories can be used for secondary purposes to analyse care processes and care modes. This information can be further used in the management e.g., to estimate nursing care competencies and educational needs at the hospitals.